The Parasite Fauna of the Gobiid Fish (Actinopterygii, Gobiidae) in the Sukhyi Lyman, Black Sea - Krasnovyd, V.; Kvach, Yu.; Drobiniak, O. (Вестник зоологии, 2012)
The parasite fauna of gobiid fish of the Sukhyi Lyman, Black Sea, is described. Seventeen species of parasites are registered in the gobiids in the water body. The marine tubenose goby Proterorhinus marmoratus has the richest parasite fauna (12 species), the grass goby Zosterisessor ophiocephalus has the fewest number of parasite species (5 species). The microsporidian Loma sp. and ciliate Trichodina domerguei are recorded for the first time for gobiids in the north-western Black Sea. The core of the parasite fauna is formed by metacercariae Cryptocotyle spp. The core, secondary, satellite, and rare species in the parasite community of each host are described. Not only marine and brackish water parasites, but also limnetic species, namely metacercariae D. spathaceum, were registered in the Sukhyi Lyman that differentiates it from the many of localities in the north-western Black Sea.